Towards the paperless office : an introduction to electronic structured document interchange : a thesis submitted to the Faculty of Technology in candidacy for the degree of Master of Technology (Computing), Department of Production Technology - Fraser, PJ (Massey University, 1992)
Despite the advances in computing technology and office automation, and forecasts of the paperless office having become a reality by now, there remains the fact that very few companies would face less paper today than they did five years ago. Offices today are still deluged with paper because current office automation technology has failed to address one aspect of paperwork common in the office environment: the electronic equivalent to structured internal paper-based documents. Electronic structured document interchange (ESDI) has been proposed as the last remaining technology in providing the complete infrastructure for the "paperless office." Complementing current electronic office system technology, including imaging technologies, electronic mail, and electronic data interchange, ESDI was designed to provide the electronic equivalent to structured internal paper-based documents. Electronic structured document interchange is the intra-company computer-to-computer processing of business transactions in a format that allows the receiver to process the transaction by traditional business practices. Fundamentally, ESDI is a data processing concept that spans a single business enterprise, providing the complete electronic equivalent to the handling and processing of internal paper-based documents. The rationale being to take advantage of the benefits of electronic processing and delivery, while retaining traditional business practices. In some respects, ESDI systems have the potential to improve business practices by providing capabilities that are simply not possible with traditional paper-based systems. This emerging technology, the justification for such a technology, and features of the technology, including details of the administrative ESDI system implemented at Massey University, are discussed.
Floppy disk is unreadable.
Keywords: Office management; Technological innovations; Office practice; Automation; Information technology